Chromhidrosis: An Unusual Cause of Skin Discoloration. Issue 12 (December 2021) - Suessman, Anna; Srinivasan, Saranya
Abstract : Abstract: Chromhidrosis is a rare condition characterized by the secretion of colored sweat. We report a case of a preadolescent healthy girl presenting with acute, recurrent blue discoloration of her armpits. The blue discoloration can be wiped off but recurs. As providers, it is useful to be familiar with this diagnosis and course of disease.